Telehealth Education via WeChat Improves the Quality of Life of Parents of Children with Type-1 Diabetes Mellitus - Huang, Mei-Xia; Wang, Mei-Chun; Wu, Bi-Yu (Applied Clinical Informatics, 2022)
Objective The purpose of this study was to explore the effect of telehealth education and care guidance via WeChat (Tencent Ltd., Shenzhen, China; a popular smartphone-based social media application) on improving the quality of life of parents of children with type-1 diabetes mellitus.Methods A prospective randomized controlled study was conducted in our hospital from March 2019 to September 2020 to compare the quality of life of parents of children with type-1 diabetes mellitus in the intervention group and the control group.Results Six months after discharge, the Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) scores of parents in the intervention group were significantly lower than those in the control group (p < 0.05). Compared with the SAS and SDS scores at discharge time, those scores of parents at 6 months after discharge time in intervention group were significantly lower (p < 0.05), while those scores of parents at 6 months after discharge time in control was similar (p > 0.05). Six months after discharge, the scores of the physiological field, psychological field, social relationship field, and environmental field in the intervention group were significantly higher than those of the control group according to the result of the World Health Organization Quality of Life Brief Scale (WHOQOL-BREF; p < 0.05).Conclusion Using WeChat to provide telehealth education and home care guidance to the parents of children with type-1 diabetes mellitus can effectively relieve the anxiety and depression of the parents and improve their quality of life.
Keywords: telehealth education; home care; type-1 diabetes mellitus; quality of life